THE MAIN DIRECTIONS OF ENSURING THE ECONOMIC SECURITY OF ENTERPRISES - Uktamov Khusniddin Fakhriddinovich; Uktamov Khusniddin Fakhriddinovich (Scholar Express Journals, 2023)
The article determines the role and the meaning of network structures in modern economy. There are revealed risks and threats in the activity of economic entities that are part of network structures. The notion of economic security in the network economy is revealed. The structure of the economic security system of network companies is formed, its basic components being characterized. Basic components of the economic security system in the network economy under current conditions are analysed, some problems of ensuring economic security and ways of their solution are determined. A complex mechanism of diagnosing the enterprise economic security is elaborated. The article considers main ways of ensuring economic entities’ security by introducing the integrated economic security system to predict and prevent threats to economic security
Keywords: : industrial enterprises; economic security; economic security of enterprises; indicators of assessment